Analysis of Independent Curriculum Based on Differentiated Learning Early Childhood Education Level - Hasibuan, Rabitah Hanum; Ningsih, Arie Dwi (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Differentiated learning has a close relationship with children's developmental achievements, especially with the abilities of the basic educational concepts of the alpha generation. when differentiated learning can be implemented well, there will be recognition and attention to individual differences between children. this allows teachers to respond specifically to each child's characteristics and learning needs. this research aims to describe teachers' reflections on the application of basic preschool concepts in implementing differentiated learning and to describe the improvements and advantages made by kindergarten teachers in implementing differentiated learning. this research uses interview techniques as data collection and documentation techniques in the form of pictures in the classroom and school environment. the data source for this research is a learning teacher at a driving school. the data was analyzed using the mil amd hubbermen data analysis technique, namely the flow analysis technique. the results of this research show that group b kindergarten teachers' reflections on differentiated learning carried out in driving schools include diagnostic assessments, content differentiation, process differentiation, and product differentiation. in more detail, the implementation experienced quite a lot of obstacles and there were even activities that were outside the provisions of the independence provisions.